EFEKTIVITAS MODEL PEMBELAJARAN ECOLITERACY DAN ADAPTASI (ELA) DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA KELAS V SDN GEDONGKUNING YOGYAKARTA - puspitasari, Rima eka; Hermawan Wahyu Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objectives of this study : 1) the increase in IPAS learning motivation between students who participated in the ELA learning model and students who participated in the Direct Instruction learning model in grade V students at SDN Gedongkuning Yogyakarta, 2) the effectiveness of the ELA model in teaching the on the topic of Harmonious Ecosystems in fifth grade at SDN Gedongkuning Elementary School in Yogyakarta. The type of research used in this study was quantitative experimental with a non-equivalent control group design. The population of this study was 56, and the sample used was 28 VA as the experimental class using the ELA model, and 28 VB as the control class using the Direct Instruction model. The data collection methods used were questionnaires and observations. The analysis techniques used were prerequisite tests using normality and homogeneity tests, followed by hypothesis testing using t-tests or difference tests with Independent Sample T-Tests.The results : 1) there was a difference in learning motivation between the control and experimental classes, with the SPSS test results showing that the average learning the experimental class were 70.25 for the pretest and 78.57 for the posttest. Meanwhile, the the control class were 74.29 for the pretest and 89.32 for the posttest. 2) The ELA learning model is effective in increasing student learning motivation in Grade 5 IPAS learning, especially in the material on harmonious ecosystems, because in data processing using the Independent Sample T-Test, a Sig. (2-tailed) value of 0.000 < 0.05 was obtained.